CX-4945 induces methuosis in cholangiocarcinoma cell lines by a CK2-independent mechanism - Jomnarong Lertsuwan (2019)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Cholangiocarcinoma is a disease with a poor prognosis and increasing incidence and hence there is a pressing unmet clinical need for new adjuvant treatments. Protein kinase CK2 (previously casein kinase II) is a ubiquitously expressed protein kinase that is up-regulated in multiple cancer cell types. The inhibition of CK2 activity using CX-4945 (Silmitasertib) has been proposed as a novel treatment in multiple disease settings including cholangiocarcinoma. Here, we show that CX-4945 inhibited the proliferation of cholangiocarcinoma cell lines in vitro. Moreover, CX-4945 treatment induced the formation of cytosolic vacuoles in cholangiocarcinoma cell lines and other cancer cell lines. The vacuoles contained extracellular fluid and had neutral pH, features characteristic of methuosis. In contrast, simultaneous knockdown of both the α and α′ catalytic subunits of protein kinase CK2 using small interfering RNA (siRNA) had little or no effect on the proliferation of cholangiocarcinoma cell lines and failed to induce the vacuole formation. Surprisingly, low doses of CX-4945 increased the invasive properties of cholangiocarcinoma cells due to an upregulation of matrix metallopeptidase 7 (MMP-7), while the knockdown of CK2 inhibited cell invasion. Our data suggest that CX-4945 inhibits cell proliferation and induces cell death via CK2-independent pathways. Moreover, the increase in cell invasion brought about by CX-4945 treatment suggests that this drug might increase tumor invasion in clinical settings.